แนวคิดงานคุ้มครองผู้บริโภคด้านสุขภาพ (CONCEPT OF HEALTH CONSUMER PROTECTION) - Chalongsuk, Rapeepun (Thai Bulletin of Pharmaceutical Sciences, 2017)
การแข่งขันทางการค้าทำให้ผู้บริโภคได้รับประโยชน์จากการมีโอกาสเลือกบริโภคสินค้า-บริการที่หลากหลาย แต่การตัดสินใจบริโภคสินค้า-บริการอย่างเหมาะสมขึ้นกับการมีรายละเอียดเกี่ยวกับสินค้า-บริการที่ครบถ้วน ดังนั้นการคุ้มครองผู้บริโภค คือการคุ้มครองการตัดสินใจของผู้บริโภคจากการตัดสินใจที่ไม่เป็นเหตุเป็นผล มาตรการต่าง ๆ ที่ใช้คุ้มครองผู้บริโภค เช่น การให้รายละเอียดเกี่ยวกับคุณภาพ ราคาของสินค้า-บริการ รวมถึงการเยียวยาความเสียหายที่เกิดจากการบริโภคสินค้า-บริการให้กับผู้บริโภค และการปรับเปลี่ยนทัศนคติในการบริโภคสินค้า-บริการให้เหมาะสม แต่ในขณะเดียวกันการคุ้มครองผู้บริโภคที่ดีต้องไม่เป็นอุปสรรคในการในการเข้าถึงสินค้า-บริการด้วย To stimulate trade competition is beneficial for consumers having a larger choice of goods and services from markets. But the consumer will have a rational decision depend on the perfect information of goods and services. Then concept of Health Consumer Protection is to prevent consumer decision from irrational behavioral decision. There are many strategies to implement the concept of health consumer protection such as making quality and price information available, receiving a fair settlement of just claims, including compensation for misrepresentation, shoddy goods or unsatisfactory services and rational attitude of goods-services consumption. However, good consumer protection system should not be a barrier to access goods and services.